Declining labor-labor exchange rates as a cause of inequality growth - Andranik S. Tangian (Karlsruher Institut für Technologie (KIT), Institut für Volkswirtschaftslehre (ECON), 2017)
The current trends in the capital/labor split and the impacts thereof on the growth of inequality are one of the main concerns of national governments, European Commission and international organizations like UN, ILO, IMF, OECD and WB. These trends are usually studied at the macro level of functional distribution of income, that is, among capital and labor, and less with regard to productivity, remuneration policies or some other particular factors. In this paper, we contribute to the studies of the second type, explaining the decreasing labor income share in terms of unpaid working time and underpaid hourly earnings. For this purpose, we refer to the decreasing labor-labor exchange rate, i.e. devaluation of one's labor in exchange for other's labor embodied in the commodities affordable for one's earnings. We show that the productivity growth allows employers to compensate workers with always a lower labor equivalent, i.e. increasingly underpay works, maintaining however an impression of fair pay due to an increasing purchasing power of earnings. This conclusion is based on the OECD 1990-2014 data for G7 countries (Canada, France, Germany, Italy, Japan, United Kingdom and United States) and Denmark (known for the world least inequality). Then statistically significant implications for the growth of inequality are derived and some policy suggestions are formulated like taxing the enterprises with the inner Gini that surpasses the national level.
urn:nbn:de:swb:90-755124
Keywords: D31; D63; E31; E64; J24; J3; O47; 330; inequality; productivity; hourly earnings; consumer prices; housing prices; labor-labor exchange rate